QUALITATIVE COMPOSITION OF COW MILK OF UKRAINIAN RED-POCKMARKED DAIRY BREED - Chernyavska, T. O.; Izmaylova, N. O. (Scientific Progress & Innovations, 2019)
The article analyzes the results of Ukrainian and foreign researchers on the breed characteristics of the qualitative composition of cow milk. It has been established that each breed is characterized by certain pecu-liarities as to the content of milk fat, protein and other components. Much attention has been paid to the presence of somatic cells in milk, which is the indicator of cow disease for mastitis. Animals of different breeds are characterized by different content of somatic cells and, accordingly, their resistance to the dis-ease. Therefore, continuous monitoring of these signs is an important measure aimed at improving the com-petitiveness of dairy cattle. That is the reason for our research on the stock of Ukrainian red-pockmarked (local) dairy breed, which is kept at the state enterprise “State agro-farm “Nadiia” of the Institute of Animal Husbandry of the National Academy of Agrarian Sciences of Ukraine. Qualitative indices were determined in the laboratory of the Institute of Animal Husbandry on the equipment of Bentley firm. As a result of the conducted researches it was established that animals of the Ukrainian red-pockmarked dairy breed have low content of fat and protein in milk, which depended on the age of cows. Primaparous cows gave milk with less content of protein, casein, dry matter and skimmed milk residue than full-aged cows. The average content of somatic cells in milk corresponded to the physiological norm. With age, the content of somatic cells in ani-mals increases. З віком сила зв’язку збільшується. The connection of different direction and level of relia-bility was established between separate qualitative indices of milk. A positive relationship was found be-tween the fat and protein content of milk, fat and dry matter, protein and casein, protein and skimmed milk residue. The relationship increases with age. Reliable negative correlation was established between the number of somatic cells in milk and the content of its individual components. Further improvement of the Ukrainian red-pockmarked dairy breed has to be directed at improving milk qualitative composition.